2018
DOI: 10.1007/s10750-018-3530-2
|View full text |Cite
|
Sign up to set email alerts
|

Histological evidence that diploid hybrids of Cobitis taenia and C. elongatoides (Teleostei, Cobitidae) develop into fertile females and sterile males

Abstract: In Europe, two bisexual fish species, Cobitis taenia (TT) and Cobitis elongatoides (EE), hybridized, producing diploid and polyploid clonal lineages. This study compared, for the first time, embryonic development, hatching success, sex ratio, body size and as well as reproductive ability based on the gonad histology of F1 reciprocal diploid hybrids (TE, ET) of both species. Hybrid F1 progeny showed the same proper pattern of embryonic and larval development. Among TE and ET offspring, slightly more females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Hybrid sterility and asexuality evolves in a sex specific manner: Mechanistically, reproductive incapacity of hybrid males is reflected by defective development of hybrid testes as evidenced by histological examination of diploid ET ( [23], this study) and triploid ETT hybrid males (this study). The…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Hybrid sterility and asexuality evolves in a sex specific manner: Mechanistically, reproductive incapacity of hybrid males is reflected by defective development of hybrid testes as evidenced by histological examination of diploid ET ( [23], this study) and triploid ETT hybrid males (this study). The…”
Section: Resultsmentioning
confidence: 85%
“…Reproductive experiments and histological observations showed that C. elongatoides-taenia hybrid females (both diploid and triploid, naturally occurring as well as artificial F1 strains) are fertile and reproduce clonally by spermdependent parthenogenesis, known as gynogenesis (i.e. they produce unreduced eggs but require sperm to activate cellular division; [9,[20][21][22][23]. Occasional fusion of sperm with hybrid egg pronuclei results in triploid progeny with EET or ETT genomic constitution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive experiments and histological observations have shown that C. elongatoides × C. taenia hybrid females (ET, 49 chromosomes) reproduce clonally through sperm-dependent gynogenesis, producing only female hybrid progeny ( i.e. , they produce unreduced eggs but require sperm to activate cellular division; summarized in Figure 1A ; Janko et al 2007a , 2018 ; Choleva et al 2012 ; Juchno et al 2017 ; Juchno and Boroń 2018 ). The occasional fusion of sperm with hybrid egg pronuclei results in triploid progeny of both sexes with EET (74 chromosomes) or ETT (73 chromosomes) genomic constitutions, but only females are able to clonally propagate ( Figure 1A ).…”
mentioning
confidence: 99%
“…The occasional fusion of sperm with hybrid egg pronuclei results in triploid progeny of both sexes with EET (74 chromosomes) or ETT (73 chromosomes) genomic constitutions, but only females are able to clonally propagate ( Figure 1A ). In contrast to their clonal sisters, the diploid (ET) and triploid (EET and ETT) male hybrids have drastically reduced reproductive capabilities, and appear to be incapable of either fertilizing normal haploid eggs or triggering the development of clonal eggs ( Figure 1A ) ( Vasil’ev et al 2003 ; Choleva et al 2012 ; Juchno and Boroń 2018 ).…”
mentioning
confidence: 99%